B Cells in the Multiple Sclerosis Central Nervous System: Trafficking and Contribution to CNS-Compartmentalized Inflammation - Michel, Laure; Touil, Hanane; Pikor, Natalia B.; Gommerman, Jennifer L.; Prat, Alexandre; Bar-Or, Amit (Frontiers in Immunology, 2015)
Clinical trial results of peripheral B cell depletion indicate abnormal pro-inflammatory B cell properties, and particularly antibody-independent functions, contribute to relapsing MS disease activity. However, potential roles of B cells in progressive forms of disease continue to be debated. Prior work indicates that presence of B cells is fostered within the inflamed MS central nervous system (CNS) environment, and that B cell-rich immune-cell collections may be present within the meninges of patients. A potential association is reported between such meningeal immune-cell collections and the sub-pial pattern of cortical injury that is now considered important in progressive disease. Elucidating the characteristics of B cells that populate the MS CNS, how they traffic into the CNS and how they may contribute to progressive forms of the disease has become of considerable interest. Here, we will review characteristics of human B cells identified within distinct CNS sub-compartments of patients with MS, including the cerebrospinal fluid (CSF), parenchymal lesions and meninges, as well as the relationship between B cell populations identified in these sub-compartments and the periphery. We will further describe the different barriers of the CNS and the possible mechanisms of migration of B cells across these barriers. Finally, we will consider the range of human B cell responses (including potential for antibody production, cytokine secretion and antigen presentation) that may contribute to propagating inflammation and injury cascades thought to underlie MS progression.